2020
DOI: 10.1021/acscombsci.0c00172
|View full text |Cite
|
Sign up to set email alerts
|

Optical Identification of Materials Transformations in Oxide Thin Films

Abstract: Recent advances in high-throughput experimentation for combinatorial studies have accelerated the discovery and analysis of materials across a wide range of compositions and synthesis conditions. However, many of the more powerful characterization methods are limited by speed, cost, availability, and/or resolution. To make efficient use of these methods, there is value in developing approaches for identifying critical compositions and conditions to be used as a priori knowledge for follow-up characterization w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Because the lg-LSA is an irreversible method, a specific position x [and potentially its associated composition c (x) in the presence of a composition gradient] can only be annealed once, further emphasizing the need for optimizing the selection of the processing conditions. Once an lg-LSA stripe is processed, a conclusive structural characterization across the thermal gradient is possible with grazing-incidence high-intensity x-ray diffraction (XRD) to resolve the crystal structure ( 47 ). However, access to synchrotron facilities capable of producing x-rays with appropriate wavelength, intensity, and micrometer-scale spatial resolution comprises an inherently limited resource that motivates development of alternative phase boundary detection methods.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the lg-LSA is an irreversible method, a specific position x [and potentially its associated composition c (x) in the presence of a composition gradient] can only be annealed once, further emphasizing the need for optimizing the selection of the processing conditions. Once an lg-LSA stripe is processed, a conclusive structural characterization across the thermal gradient is possible with grazing-incidence high-intensity x-ray diffraction (XRD) to resolve the crystal structure ( 47 ). However, access to synchrotron facilities capable of producing x-rays with appropriate wavelength, intensity, and micrometer-scale spatial resolution comprises an inherently limited resource that motivates development of alternative phase boundary detection methods.…”
Section: Resultsmentioning
confidence: 99%
“…To address this issue, we developed a complementary technique based on microscopy imaging and optical spectroscopy to rapidly assess phase boundaries. We recently demonstrated that structural phase changes are directly associated with changes in the optical thin-film properties of transparent films, in particular the optical thickness nd ( 47 ), where n is the refractive index and d is the film thickness. Essentially, the gradients of the optical measurements across an lg-LSA stripe provide a means to map out phase boundaries without explicit crystallographic phase identification, thereby producing an unlabeled processing phase diagram without costly XRD experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of the composition−optical relationships with measured phase behavior indicates that the composition region of double perovskite phase formation can be identified with optical analysis, a strategy for accelerating identifying phase transitions that was recently reported for combinatorial variation of thermal processing conditions (as opposed to variation of 4-cation composition in the present work). 26 This stratregy combined with the high throughput synthesis and optical imaging techniques enabled our rapid screening of 9 additional 4-cation oxide composition spaces to demonstrate that this type of Bi alloying is quite general. The ink solvent was 15 vol % diethylene glycol in water, and each sample was formed by controlled mixing of one to four inks with a total dispensed volume for each sample of ∼50 pL.…”
Section: ■ Introductionmentioning
confidence: 99%
“…We report a high-throughput workflow for discovering candidate compositions for functional properties by coupling high-throughput synthesis and optical characterization with automated data interpretation. Parallel optical screening was recently demonstrated as a proxy for phase behavior in the context of combinatorial thermal processing of individual compositions ( 30 ). We extend this approach to high-order composition spaces using inkjet printing ( 31 ) to deposit composition-gradient lines of material that are subsequently imaged by a purpose-built hyperspectral microscope that measures optical absorption from the infrared to ultraviolet (UV).…”
mentioning
confidence: 99%